PENERAPAN PENDEKATAN SOMATIS, AUDITORI, VISUAL, INTELEKTUAL (SAVI) DAN MEDIA GAMBAR SERI DALAM PENINGKATAN KETERAMPILAN MENYIMAK CERITA PADA SISWA KELAS V SD NEGERI 1 KEBUMEN TAHUN AJARAN 2013/2014 - Yuliani, Ani (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract. The application of Somatic, Auditory, Visual, Intellectual (SAVI) approach and picture series media in upgrading story listening skills at V grade students of State Elementary School 1 Kebumen in academic year 2013/2014. The purpose of this research is to upgrading story listening skills Elementary School V grade students by application SAVI approach and picture series media. This research is Classroom Action Research (CAR) collaborative. The research was conducted in three cycles which every cycles is consist of planning, acting, observing, and reflecting. The subject of this research were 37 students V grade of Elementary School 1 Kebumen who were 16 males and 21 females. The validity of the data using triangulation of sources and techniques. The results of this study concluded that the application of SAVI approach and picture series media which done exact of the step can be upgrading story listening skills at V grade students of State Elementary School 1 Kebumen in academic year 2013/2014.Keywords: SAVI Approach, Picture Series, Listening Skills